GENETIC MEDICINES IN INDIA: BLESSING OR CURSE? - Kanniyakonil, Scaria (Asian Horizons, 2013)
Genetics grows so rapidly. Every month we receive a new announcement about the scientific achievement from the genetical research in plants, animals and human beings. Compared to other medical technologies, genetics can radically change the nature of environment and the nature of human being. Today we have genetically engineered trees, plants, animals, food, insects, bacteria and viruses. Genetic medicines also proved the origin of genetic diseases and the functions of genes. Genetic testing and screening, genetics therapy, genetic design and enhancement are the few developments in genetic medicine. Genetic engineering is so common and we live in the midst of it. There are many merits as well as demerits in genetics. The problems in genetics are very complex and complicated and raise many ethical and moral theological issues. In this context this paper is about “Genetic Medicines in India: Blessing or Curse?” We make an ethical evaluation on genetic medicines. We divide this paper into three sessions. The first session discusses a short view on genetic medicines in India. The second part describes ethical issues in genetics and the third part is an ethical appraisal of genetic medicines.